Pendidikan Musik sebagai Wahana Pendidikan Nilai - Agung Dwi Putra; Sofyan Sauri; Aceng Kosasih (Program Studi Pendidikan Musik FBS UNP, 2022)
This article seeks to provide readers with a comprehensive understanding that Music Education is actually a vehicle for Value Education because it presents good values ​​that can be internalized by a person so that a positive character is built. The research was conducted by reviewing the relevant literature so that the results can be described as answers that build a certain theoretical framework. The relevant literature in question is obtained from various written sources originating from journals, books, and web pages (internet). The entire literature is then reviewed, filtered to see its relevance, interpreted, described, reinterpreted, and described as an answer that explains the concept of Music Education as a vehicle for Values ​​Education. This study found that Music Education is a very important element as a vehicle for value learning, regardless of its implementation which has certain standards as regulated in NAfME as a Music Education organization in the world based in the United States. In the national context, Ki Hadjar Dewantara has always seen the importance of Music Education as a vehicle for Value Education through his conception of Gending and Wirama.